Ce/Sm/Sr-Incorporating Ceramic Scaffolds Obtained via Sol-Gel Route - Jinga, Sorin-Ion (Materials (Basel), 2021)
Three different inorganic scaffolds were obtained starting from the oxide system SiO(2)‒P(2)O(5)‒CaO‒MgO, to which Ce(4+)/Sm(3+)/Sr(2+) cations were added in order to propose novel materials with potential application in the field of hard tissue engineering. Knowing the beneficial effects of each element, improved features in terms of mechanical properties, antibacterial activity and cellular response are expected. The compositions were processed in the form of scaffolds by a common sol-gel method, followed by a thermal treatment at 1000 and 1200 °C. The obtained samples were characterized from thermal, compositional, morphological and mechanical point of view. It was shown that each supplementary component triggers the modification of the crystalline phase composition, as well as microstructural details. Moreover, the shrinkage behavior is well correlated with the attained compression strength values. Sm was proven to be the best choice, since in addition to a superior mechanical resistance, a clear beneficial influence on the viability of 3T3 fibroblast cell line was observed.